Earnings dynamics and its intergenerational transmission: Evidence from Norway - Elin Halvorsen; Serdar Ozkan; Sergio Salgado (Quantitative Economics, 2022)
Using administrative data, we provide an extensive characterization of labor earnings dynamics in Norway. Some of our findings are as follows: (i) Norway has not been immune to the increase in top earnings inequality seen in other countries, (ii) the earnings distribution compresses in the bottom 90% over the life cycle but expands in the top 10%, and (iii) the earnings growth distribution is left-skewed and leptokurtic, and the extent of these nonnormalities varies with age and past income. Linking individuals to their parents, we also investigate the intergenerational transmission of income dynamics. We find that children of high-income, highwealth fathers enjoy steeper income growth over the life cycle and face more volatile but more positively skewed income changes, suggesting that they are more likely to pursue high-return, high-risk careers. Income growth for children of poorer fathers is more gradual and more left skewed, displaying higher left tail risk. Furthermore, the income dynamics of fathers and children are strongly correlated: children of fathers with steeper life-cycle income growth, more volatile incomes, or higher downside risk also have income streams of similar properties. These findings shed new light on the determinants of intergenerational mobility
Keywords: E24; J24; J31; 330; Earnings dynamics; top income inequality; heterogeneity; intergenerational mobility